Local and distal changes in dynamics are caused by an L205R Cushing’s syndrome mutant in PRKACA - Anagha Kalle; Jian Wu; Caesar Tawfeeq; Alexandr P. Kornev; Gianluigi Veglia; Rodrigo Maillard; Susan S. Taylor; Nisha Amarnath Jonniya (Proceedings of the National Academy of Sciences, 2025)
Cushing’s syndrome (CS) is an abnormal condition characterized by elevated cortisol levels, often resulting from genetic alterations in the PRKACA gene, which encodes the catalytic subunit of cAMP-dependent protein kinase A (PKA-C). The most common CS mutation, L205R, lies at the P + 1 loop. Understanding how this mutation alters the internal allosteric network within PKA-C and changes nucleotide and substrate cooperativity is a major goal. Using molecular dynamics (MD) simulations and protein residue networks based on local spatial pattern (LSP) method, we compare crystal structures of wild-type PKA-C and L205R. Our findings indicate that L205R not only locally disrupts the P + 1 hydrophobic pocket, leading to the displacement of the P + 1-residue and altered substrate specificity, but also has long-range effects in the linker connecting the A helix to β strand 1. The MD simulations and LSP analyses also reveal critical changes at the phosphoryl transfer site. Some of these changes are captured in the L205R crystal structure while others are not. With this strategy, we also show how the dynamics of local and distal allosteric networks are differentially influenced by backbone and side-chain dynamics.